STEREOTIP DAN DAMPAKNYA DITENGAH KEHIDUPAN SOSIAL MASYARAKAT - Amanda Rosetia; Renny Christiarini; Nur Hidayati; Jevin Tan; Muhammad Fadhil Karuniansyah; Kelvin Hendra Lim; Nurhafnil Hayati; Sarah Lena Mariosta; Davin Davin; Aviany Yanti; Erni Erni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
Indonesia is famous for its cultural diversity. Living among these cultural diversity causes many conflicts. One of the main reasons is stereotype, which is a prejudice carried out by other individuals or groups without facts. And was very often found in the community environment people who were kind, was judge rude just because of the intonation of a rough speech. Therefore, through the Social Empowerment program, SEPORA 2020, we use social media as an educational media to build awareness in the community to avoid stereotypical views. From the results obtained through the media named we.changeit, it made the public enthusiastic in preventing stereotypes. For the next prototype, we plan to podcast-related speakers.